The Impact Of Fiscal Policy On Private Investment And Economic Growth In Nigeria - Yusuf, Abdul Karim (2021)
In the literature neither taxes, government spending nor deficits are robustly correlated with economic growth when evaluated individually. The lack of correlation can emerge from the inability of any single budgetary factor to completely capture the stance of fiscal policy. Confirming the findings of previous literature, thus allowing for a more in-depth disaggregation of fiscal policy variables, this thesis, focused on the pair-wise combination of fiscal indicators, investigated the effect of fiscal policy on private investment and economic growth in Nigeria using annual data from 1980 to 2017. Although studies on the linear relationship between fiscal policy variables and economic growth have been developed in the past, the empirical strategy of the current research departs from this approach and explored the symmetrical and asymmetrical effects of the variables tested using linear and nonlinear ARDL methods to assess the presence or otherwise of any long-term relationship and the direction of causality between them. Based on empirical evidence, direct taxes prompted a significant negative effect on private investment and economic growth, while indirect taxes produced a significant positive impact on private investment and economic growth. Recurrent expenditure decelerated private investment but stimulated growth, while capital expenditure encouraged private investment but suppressed economic growth. For disaggregated public debt, domestic debt was associated with an insignificant positive impact on private investment and a significant adverse effect on growth.